Boswellia serrata Extract as an Antibiofilm Agent against Candida spp - Jaroš, Petr; Vrublevskaya, Maria; Lokočová, Kristýna; Michailidu, Jana; Kolouchová, Irena; Demnerová, Kateřina (Microorganisms, 2022)
The use of antibiotics or antifungals to control infections caused by pathogenic microorganisms is currently insufficiently effective because of their emerging resistance. Thanks to the ability of microorganisms to form a biofilm and thus increase their resistance to administered drugs even more, modern medicine faces the task of finding novel substances to combat infections caused by them. In this regard, the effects of essential oils or plant extracts are often studied. Among the relatively neglected plants is Boswellia serrata, which has a high content of biologically active boswellic acids. In this study, we focused on one of the most common nosocomial infections, which are caused by Candida species. The most common representative is C. albicans, although the number of infections caused by non-albicans species has recently been increasing. We focused on the antifungal activity of Boswellia serrata extract Bioswellix against planktonic and adhering cells of Candida albicans, Candida parapsilosis and Candida krusei. The antifungal activity against adhering cells was further explored by determining the metabolic activity of cells (MTT) and determining the total amount of biofilm using crystal violet. Boswellic acid-containing plant extract was shown to suppress the growth of a suspension population of all tested Candida species. Boswellia serrata extract Bioswellix was most effective in inhibiting C. albicans biofilm formation.
Keywords: Candida krusei; Candida albicans; fluconazole; Candida parapsilosis; biofilm; boswellic acid